Evaluation of Fermentation Using Ma-11 on The Nutrirional Content of Palm Leaves - Prasetyo, Ardina Nur; Sukaryani, Sri; Yakin, Engkus Ainul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to determine the effect of fermentation of oil palm leaf content using MA-11 on dry matter (BK), crude protein (PK) and crude fibre (SK) content. This study uses a comprehensive randomized design (RAL) The pattern was in line with the treatment as many as four treatments and each treatment was repeated three times. T0 : 250 grams of palm oil leaves + 6cc MA-11 with an incubation period of 0 days, T1 : 250 grams of palm oil leaves + 6cc MA-11 with an incubation period of 3 days, T2: 250 grams of oil palm leaves + 6cc ma-11 with an incubation period of 6 days. T3 : 250 grams of palm oil leaf +6cc ma-11 with an incubation period of 9 days. Observed variable dry matter , crude protein, crude fibre. The results of the study showed that the average value of BK was obtained T0: 86.86%, T1: 87.76%, T2: 88.93% and T3: 90.06%, Tilapia PK was obtained T0: 5.34%, T1: 6.04%, T2 6.01% and T3 12.09% The average value of SK was obtained T0: 23.12%, T1: 21.51%, T2: 20.30% and T3: 18.27%.The conclusion from this study is that the fermentation period of 0 to 9 days using ma-11 with a dose of 6cc has a very real effect on the dry matter content and crude protein content and is able to reduce the crude fiber content.